Strategi Komunikasi Pemasaran “Iro Rumah Kopi” dalam Memperkuat Brand Awareness - Nasywa Damayanti; Shafira Rixas Febriana; Tria Patrianti (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
The coffee shop industry in Indonesia is experiencing rapid growth, leading to increasingly intense market competition, particularly among small and medium enterprises. Iro Rumah Kopi, an UMKM located in Lebak Bulus, is required to implement effective marketing communication strategies to strengthen its brand awareness. This study aims to analyze digital marketing communication practices conducted through social media platforms, especially Instagram and TikTok, which are widely used to reach young and urban audiences. A descriptive qualitative approach is applied to examine the content shared by the marketing team, focusing on messages, visual elements, storytelling techniques, and patterns of audience interaction. The results indicate that marketing communication plays a crucial role in shaping consumer perceptions and increasing brand visibility. Visual content combined with consistent storytelling and active engagement with followers successfully enhances audience interaction. The positioning of Iro Rumah Kopi as a “second home” emerges as a central message that fosters emotional connections with customers. Overall, the study concludes that consistent, creative, and relevant digital communication strategies significantly contribute to improving brand awareness and customer attachment.